Internationale økonomisk-politiske tiltag under covid-19-krisen - Rasmus Mose Jensen; Nicolai Risager Christensen; Thomas Pihl Gade; Niels Bartholdy; Helle Eis Christensen (Danmarks Nationalbank, 2020)
– Exceptionally large monetary and fiscal policy measures have been implemented globally to counteract the adverse economic consequences of the covid-19 crisis. The analysis first provides an overview of some of the measures taken to support liquidity and lending in the US, Germany, Sweden and Denmark. It then focuses on fiscal measures in the countries' stimulus packages that support demand directly. Finally, the use of state aid in the EU during the crisis is examined.
Keywords: 330; Geldpolitik; Finanzpolitik; Antizyklische Finanzpolitik; Coronavirus; Dänemark; Deutschland; Schweden; USA